PROTECTING WORKERS' HEALTH FROM OCCUPATIONAL NOISE POLLUTION IN THE MODERN TECHNOLOGICAL ERA: THE NEED OF THE HOUR (Lex localis - Journal of Local Self-Government, 2024)
Pollution is the result of the modern technology and machinery era, as well as human uncontrolled activities and unlimited aspirations. Any form of pollution negatively impacts human health, both physical and mental. Noise pollution is a form of environmental pollution, and deserves to be taken as seriously as other forms of pollution. Due to a lack of awareness about the serious adverse effects of noise pollution, it is often overlooked, even though it poses a threat to life and health as a silent killer. Loud and undesirable noise generated at the workplace also falls within the definition of noise pollution. Excessive noise at the workplace impacts the physical and mental health of workers. Noise pollution can lead to serious physical and mental health problems, such as hearing loss, heart disease, high blood pressure, insomnia, increased stress, emotional distress, and behavioural problems. Noise pollution at the workplace also negatively impacts workers' concentration, productivity, and work quality. In certain industries, this level exceeds the maximum threshold of severity. In the modern age of technology and machinery, the desire for greater and faster productivity in workplaces is fuelled by the use of newer and more advanced machinery. Noise pollution violates the fundamental human rights of the working class. Various international and national instruments have enshrined workers' rights, maximum workplace noise limits, and appropriate safety measures. In this modern era, workers' health can be protected from noise pollution through the use of the latest technologies, innovations, and safety equipment. This research paper outlines the health problems faced by workers due to workplace noise pollution and offers suggestions for addressing the problem.